Construction and optimization method of the open-pit mine DEM based on the oblique photogrammetry generated DSM. (February 2020) - Wang, Jiaheng; Wang, Liguan; Jia, Mingtao; He, Zhengxiang; Bi, Lin
Highlights: An improved method of DSM model is proposed to adapt it to the 3D mining software. Proposed a sampling method based on lacal standard deviation to analyze the DSM. Designed a terrain break points determination method considering terrain changes. This work fills the blank of such research in the field of open-pit modelling. Abstract: The digital surface model (DSM) of open-pit mines generated by oblique photogrammetry has a large amount of data and much interference information. Therefore, it is necessary to construct a 3D model with a small amount of data that can reflect the real terrain of open-pit mines. The model should adapt to the existing 3D mining software and provide a guarantee for the subsequent production planning and open-pit mine design. Taking three different complexity scenes in two open-pit mines with 1:500 mapping scale as experimental objects, we realized the DEM construction of the DSM in different scenarios in open-pit mines. The extraction completeness of mining equipment in the DSM using this method is 94.7%. The data can be compressed to approximately 0.02% of the original data. The accuracy of 210 check points in the model is consistent with the industry standard. The DEM model can be quickly imported into 3D mining software.